PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK DENGAN METODE PERMAINAN SESIKU UNTUK PENGETAHUAN FENOMENA GEMPA BUMI SISWA SD KABUPATEN KEPAHIANG - Hasnawati Hasnawati; Dwi Anggraini; Fairus Sabrina (Universitas Bengkulu, 2021)
This research aimed to discribe the development procedure and know eligibility of thematic learning tool by the Sesiku game method contained earthquake phenomena for Kepahiang elementary students. This reaseacrh was Reaseach and Development (R&D) which used ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. Thematic learning syllabus, lesson plan, and teachers’ guideline books validation; the sheet of practicality teachers’ guideline questionnaire and the practicality of thematic learning tool implementation; and the effectiveness of implementation thematic learning tool in Sesiku game worksheet were used as the intrument of this research. In this research, 87,5% were the validity of thematic learning syllabus, 86,11% for lesson plan, and 90,63% for teachers’ guideline book in Sesiku game. All the percentages showed that thematic learning tool in Sesiku game was categorized in validity. In examining of teachers’ practically guideline book in Sesiku game, the percentage was 96,43%, and 96,54% for implementation of Sesiku game as learning tool. It was categorized definitely pratical. While the examining in social (IPS) subject about the effectiveness, the researchers found 84,61%, 92,31% for Indonesian subject, and 84,61% for science (IPA) subject. From all percentages, it showed that was very effective. It concluded that thematic learning tool in Sesiku game for earthquake phenomena was eligible.